0.7 % error rate 3A bidirectional current sensor using high voltage CMOS process. (August 2021) - Wang, Chua-Chin; Lou, Pang-Yen; Hou, Zong-You; Tsai, Hsiu-Chun
Abstract: This investigation demonstrates a high-accuracy bidirectional high-voltage (HV) current sensor fabricated using CMOS technology. Besides Noise filter, Sense stage, and Controller, the proposed sensor is featured with a Switching Network composed of transmission gates, which is able to steer the direction of the current for bidirectional sensing. A digital feedback loop comprises Controller generating a pair of digital signals to Switching Network such that the direction of the current is detected real time. The area of the proposed sensor on silicon is 1173 × 664 μm 2 fabricated by 0.5 μm high-voltage CMOS process. The sensing voltage error is 0.7% by physical measurements, where the input voltage range is 8–14 V, and the current sensing range is -3 – 3 A.